A Mixed-Methods Study Into the Discipline-Specific Effect of Critical EAP on Reading Comprehension - Tahereh Movahhedi; Seyyed Amir Hossein Sarkeshikian; Mohammad Golshan (Journal of Modern Research in English Language Studies)
Although critical English for academic purposes (CEAP) has grown theoretically, more research is needed to explore it in more depth. This sequential mixed-methods study primarily aimed to examine whether the CEAP and traditional English for academic purposes (EAP) have different impacts on Iranian university students' English reading comprehension, and (if yes) whether it is discipline-specific. This study also intended to explore how traditional EAP students’ preferences aligned with the CEAP principles. To this end, a sample of 100 Iranian university students of computer sciences and architecture with intermediate level of English proficiency was initially selected through convenience sampling. They were then randomly assigned to two control groups and two experimental groups, consisting of 25 participants each. Then, two piloted researcher-made reading tests were administered to all groups as a pre-test. The experimental computer sciences and architecture groups were taught using the CEAP pedagogy. Hence, the syllabus was negotiated based on the CEAP principles. The control computer sciences and architecture groups received the traditional EAP as their placebos. They were taught the curricular textbooks. After the treatment, all groups were asked to complete their posttests. Two-way ANOVA results indicated that the CEAP groups significantly outperformed the traditional EAP groups on the posttests. It was also found that the effect of the CEAP pedagogy was not discipline-specific. Additionally, the results of qualitative data analysis revealed a lack of preference for the traditional EAP programs among the interviewees in favor of the CEAP. Implications are offered for EAP teachers, students, and material developers.